Formation clinique et évaluation dans un dispositif en e-learning, quel compromis? - Brigitte Charrier; Laure Lafage (Centre National d'Enseignement à Distance, 2018)
We wonder about the issue of assessment in a clinical teaching device at university. We revisited our students' works using the methods of clinical research. Considering that formative temporality is different from institutional temporality, we question the teacher's psychic posture: how can a teacher deal with the paradoxical temporalities of assessment? In order to answer the question, we make use of the narcissism's theory for analyzing our research material. We present our study following three sections: the first one describes the clinical teaching device, the second part presents the material used in the study and how they were analyzed. Then, we show how our contribution could concern any other trainer reflecting on assessment in the framework of the numerical system.